2017
DOI: 10.1103/physrevb.96.104432
|View full text |Cite
|
Sign up to set email alerts
|

Criticality and phase diagram of quantum long-range O( N ) models

Abstract: Several recent experiments in atomic, molecular and optical systems motivated a huge interest in the study of quantum long-range systems. Our goal in this paper is to present a general description of their critical behavior and phases, devising a treatment valid in d dimensions, with an exponent d+σ for the power-law decay of the couplings in the presence of an O(N ) symmetry. By introducing a convenient ansatz for the effective action, we determine the phase diagram for the N -component quantum rotor model wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
178
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(193 citation statements)
references
References 60 publications
15
178
0
Order By: Relevance
“…This is consistent with the results of [64] where it has been shown that for 3  a the phase transition is in the universality class of the SR Ising transition, see also [85,91]. Actually, taking into account corrections beyond mean-field, the threshold for the onset of the SR universality class can be put at α=2.75 [89,106,107].…”
Section: Scaling Along the Fm Critical Linesupporting
confidence: 90%
“…This is consistent with the results of [64] where it has been shown that for 3  a the phase transition is in the universality class of the SR Ising transition, see also [85,91]. Actually, taking into account corrections beyond mean-field, the threshold for the onset of the SR universality class can be put at α=2.75 [89,106,107].…”
Section: Scaling Along the Fm Critical Linesupporting
confidence: 90%
“…The present FRG approach has the indisputable advantage to capture, within a single calculation a consistent picture for the SSB transition in the whole d, σ and N parameter space, as a down side the topological phase transition which shall occur for σ = 2 in d = 1 can only be addressed within the present formalism [117]. In passing we note that the MC results for a quantum XY model coupled to an anomalous Bosonic bath [118] seem to provide a value σ * = 2 − η with η = 1 4 even for the N = 2, which is consistent with the BKT scenario [see [119] for a recent numerical study of the dilute LR XY model].…”
Section: The Critical Exponentsmentioning
confidence: 99%
“…In this work, we deal with the previous issues by first considering the case of classical O(N ) models in dimension d ≥ 2 for weak LR interactions, see Sections II-III. The goal of these sections is to review the FRG treatment for classical models and to set up the ground for the study of the quantum case, which is the subject of Sections IV-IV C. Our presentation is based on the formalism developed and the results obtained in [27][28][29], while the presentation follows the one in [30]. Our main objectives is to present such findings in an unified and compact way, providing as well details on the derivations and new results on the topic of weak LR spin systems.…”
mentioning
confidence: 99%
“…Then, it would be more convenient to consider different regularization schemes which deliver considerably simpler functional flow equations [33]. Another interesting perspective is the study of the nonunitary family of fixed points generalizing the LPA analysis [34] or long range interacting field theories, both in the classical [35] and quantum case [36,37] or, finally in presence of global symmetries as OðNÞ interactions [8,9,15] or Potts model S nþ1 -symmetries [38]. We leave all these applications to future works.…”
Section: Discussionmentioning
confidence: 99%